Tanaman Kopi Sebagai Penopang Penting dalam Nilai Ekspor Komoditas Perkebunan Indonesia - Achmad Andi Leanado; M Aditya Ferdiansyah; Ikke Adelia Amanda; Shinta Putri Marvina; Alvine Wijaya UN; Arga Christian Sitohang (Journal of Economics, Management, and Accounting, 2026)
Coffee is one of Indonesia’s strategic plantation commodities with a substantial role in supporting national export performance. Beyond increasing global demand for Arabica and Robusta varieties, coffee exports demonstrate a close linkage with the overall dynamics of agricultural export values. This study aims to examine correlation between coffee export value and non-coffee agricultural export value in order to assess the strategic position of coffee as a supporting pillar of Indonesia’s plantation export sector. The research employs a quantitative approach using Pearson Product Moment correlation analysis based on monthly time-series data from January 2022 - December 2024. The variables analyzed include coffee export value (X), total agricultural export value excluding coffee (Y), along with their squared values and cross-products. The findings indicate coffee exports play a significant role in reinforcing stability of agricultural export performance. Integrated policy support and modernization of the coffee industry are therefore essential to sustain Indonesia’s competitiveness in the global market.